Toxic Stress in a Mid-Sized Urban Community: An Initial Needs Assessment of Families with Children in Maywood, IL. (July 2021) - McCune, Erin; Wojtowicz, Jennifer; Adams, William; Sigman, Garry; Williams, Collette; Ahn, Pauline; Ciliberti, Ashley; Hatchett, Lena; O'Keefe, Julie
Background: Loyola Medical Center is located in Maywood, IL, a community that faces high rates of poverty, violence, and barriers to healthcare. These factors can contribute to toxic stress, which has been shown to negatively impact children's health. Objectives: The goal of this project was to partner with community organizations to obtain a baseline needs assessment from families in Maywood regarding sources of toxic stress and to identify interventions of interest. Methods: In total, 75 anonymous surveys were collected from the Loyola Outpatient Center Pediatric Clinic and a Maywood community center. Survey responses were statistically analyzed in order to determine toxic stressors most commonly impacting families in Maywood as well as interventions of most interest to the community. Results: There were 78 respondents for a response rate of approximately 71%. The most common stressors were smoking in the home (33.3%), food insecurity (29.5%), and exposure to violence (26.9%). In this sample, Black respondents were 11.5 times more likely than non-Black respondents to report that their child was exposed to violence in the community – even after controlling for concern about their child's behavior which served as a surrogate measure of the child's exposure to toxic stress (P = 0.001). Further, those living with food insecurity were 7.40 times more likely to report that access to food and transportation vouchers were important ( P  < .001). For every 1-point increase in the total toxic stress score, respondents were 1.35 times more likely to report that increasing access to mental health resources was important to them, though this was not significant ( P  = .10). Conclusion: The data demonstrate that toxic stressors, health risks and unmet social needs are prevalent in the Maywood community, which puts local children at risk for future adverse health outcomes. With this information, pediatricians at Loyola Medical Center can work with community organizations to allocate resources to address toxic stressors in Maywood.